2018
DOI: 10.3168/jds.2018-14696
|View full text |Cite
|
Sign up to set email alerts
|

Method for short-term prediction of milk yield at the quarter level to improve udder health monitoring

Abstract: Udder health problems are often associated with milk losses. These losses are different between quarters, as infected quarters are affected both by systemic and pathogen-specific local effects, whereas noninfected quarters are only subject to systemic effects. To gain insight in these losses and the milk yield dynamics during disease, it is essential to have a reliable reference for quarter-level milk yield in an unperturbed state, mimicking its potential yield. We developed a novel methodology to predict this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
0
16
2
Order By: Relevance
“…Penry et al (2018) showed that there are significant associations between quarters for individual milking events, but they did not consider longitudinal data characteristics. Nevertheless, our earlier work (Adriaens et al, 2018) showed that both the peak yield and the persistency in unperturbed milk yield curves differ across front and hind quarters, and that the variability in quarter lactation shapes suggest that udder asymmetry and past infections may cause the expected milk yield of the left and right udder quarters to be different.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Penry et al (2018) showed that there are significant associations between quarters for individual milking events, but they did not consider longitudinal data characteristics. Nevertheless, our earlier work (Adriaens et al, 2018) showed that both the peak yield and the persistency in unperturbed milk yield curves differ across front and hind quarters, and that the variability in quarter lactation shapes suggest that udder asymmetry and past infections may cause the expected milk yield of the left and right udder quarters to be different.…”
Section: Methodsmentioning
confidence: 84%
“…Quarter separation additionally provides a unique opportunity to study losses and dynamics in the different quarters separately and to distinguish local (i.e., related to the local inflammatory reaction and toxins) and systemic (i.e., related to the general sickness) effects of the infection (Adriaens et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used the theoretical shape of the lactation curve (ULC) of AMS-milked dairy cows in the first 305 days to identify and characterize perturbations in the daily milk yield dynamics. To this end, we implemented an iterative, but computationally highly efficient method to estimate the presumed unperturbed lactation curve using the gamma function with three parameters (Wood model), as also proposed in Adriaens et al (2018, 2020) and Ben Abdelkrim et al (2019). Several other methods were tested for this study, including a 4 th order quartile regression model as proposed by Poppe et al (2020) and the Dijkstra lactation model (Dijkstra et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Wood’s model consists of 3 parameters, from which the a parameter mainly determines the scaling of the curve, whereas b and c specify the moment of peak production and slope. We preferred the Wood model over other lactation models because of its simplicity, its stability in the presence of missing data, the computational ease and its suitability for the purpose of this study (Adriaens et al, 2018; Ben Abdelkrim et al, 2019). To estimate the ULC that represents the milk production potential in absence of perturbations, an iterative fitting procedure was implemented to gradually remove milk yield data during perturbations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation